2015
DOI: 10.1039/c5cp01876e
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced homogeneous and heterogeneous triplet–triplet annihilation by gold nanoparticles

Abstract: We report the investigation of surface plasmon induced enhancement of homogeneous and heterogeneous triplet-triplet annihilation (TTA) by gold nanoparticles (AuNPs). Results show that AuNPs enhance the overall efficiency in both cases. Excitation rate and intersystem crossing efficiency of the sensitizer, and efficiency of energy transfer between sensitizer and acceptor are believed to be enhanced by the surface plasmon of AuNPs, leading to the enhancement of overall TTA efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…As a consequence of both the above processes, the singlet oxygen generation yields increase by about 10%. Our results are consistent with that reported by Cao et al 39 who have shown that the presence of Au-NPs enhanced the singlet oxygen generation of a dye conjugated with NPs relative to that in the system with a nonconjugated dye. The value of f D obtained in this study is lower than that of the rose bengal (RB) dye-Au-NP investigated system, 39 but we have a physical mixture of dyes and NPs whereas Au-NPs were conjugated with RB which influence the mechanism of ET and the possibility of the photoinduced electron transfer.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As a consequence of both the above processes, the singlet oxygen generation yields increase by about 10%. Our results are consistent with that reported by Cao et al 39 who have shown that the presence of Au-NPs enhanced the singlet oxygen generation of a dye conjugated with NPs relative to that in the system with a nonconjugated dye. The value of f D obtained in this study is lower than that of the rose bengal (RB) dye-Au-NP investigated system, 39 but we have a physical mixture of dyes and NPs whereas Au-NPs were conjugated with RB which influence the mechanism of ET and the possibility of the photoinduced electron transfer.…”
Section: Resultssupporting
confidence: 93%
“…It corresponds well to the course of quenching fluorescence and energy transfer dependencies. The value of f D obtained in this study is lower than that of the rose bengal (RB) dye-Au-NP investigated system, 39 but we have a physical mixture of dyes and NPs whereas Au-NPs were conjugated with RB which influence the mechanism of ET and the possibility of the photoinduced electron transfer. However, the results suggest that the perturbation to the local electromagnetic field in the system containing Au-NPs could enhance the spin-orbit coupling, i.e.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…65 Alternatively, the excitation rate of the sensitizer and even the emission rate of the emitter may be enhanced by the presence of plasmonic resonances locally increasing the electric field. 66,67 The TTA-UC enhancement by plasmonic effect has been realized by Poorkazem et al , 68 Baluschev et al 69 and Xian et al 70 with significant increase in TTA-UC achieved.…”
Section: Discussionmentioning
confidence: 95%
“…The fluorescence enhancement can be explained mainly by the acceleration of the radiative decay rate from the excited state by plasmon–exciton coupling as well as the photoexcitation enhancement. Recently, the emission generated via the TTA-UC phenomenon was successfully enhanced by the effect of the LSP resonance of noble metal nanoparticles. Although the enhancement of the photoexcitation efficiency of sensitizer is expected to enhance the emission, the mechanism for the enhancement in the case of the TTA-UC systems is still unclear. The effect of LSP resonance on TTA-UC can be quite complex because TTA-UC includes complicated multiple photoinduced processes.…”
mentioning
confidence: 99%